The joint venture and its activities: the joint venture in the field of finance - Abdul Kadir, Abdul Halim; Zakaria, Mohammad Ikram; Ramlan, Muhammad Azzri Rifqi; Azlan, Muhammad Syauqi; Wan Zulkurnain, Wan Muhammad Nasrul Haq (2024)
Slide Presentation: “The joint venture and its activities: the joint venture in the field of finance”